#PRS: A Study of Plastic Surgery Trends With the Rise of Instagram - Kometh Thawanyarat; Chandler Hinson; Diego A Gomez; Mallory Rowley; Yelissa Navarro; Chandler Johnson; Chelsea M Venditto (Aesthetic Surgery Journal Open Forum, 2023)
Abstract BackgroundInstagram (Menlo Park, CA) has become a popular means of advertisement for aesthetic surgery procedures, influencing patients’ likelihood of undergoing a procedure. In this study, the authors aim to explore public interest in aesthetic procedures before and after the Instagram platform started gaining in popularity through Google Trends (Google, Mountain View, CA), a platform with previously demonstrated utility for tracking interest in surgical procedures. ObjectivesThe authors hypothesize that as a result of increased medical marketing on Instagram, there is an increase in public interest in elective procedures of plastic surgery. MethodsTrends in the United States for given search terms and volumes were gathered through Google Trends between April 2004 and January 2022. Search terms included popular aesthetic procedures based on the 2020 Aesthetic Plastic Surgery National Data Bank Statistics. The search volumes were normalized, and a bivariate regression analysis of panel data was then applied to the aggregate trendlines to determine whether a statistically significant change in search volume occurred following the increase in user traffic of the Instagram platform. ResultsThe authors found significant variations in search volume for plastic surgery procedures before and after April 2012. Blepharoplasty, Botox, brachioplasty, breast implant removal, breast reduction, brow lift, butt lift, hair transplantation, lip augmentation, male breast surgery, mastopexy, mentoplasty, otoplasty, platysmaplasty, rhinoplasty, and thighplasty (PP ConclusionsThe authors observed a significant increase in public interest in both surgical and nonsurgical aesthetic procedures after Instagram gained popularity in the April of 2012.